Dynamic reserve power point tracking in grid-connected photovoltaic power plants - Narang, Aditi (2023)
This article introduces a dynamic power reserve control methodology called reserve power point tracking (RPPT) for grid-connected photovoltaic (PV) plants. The proposed RPPT methodology is employed to ensure availability of the required power reserve to support the grid and accordingly facilitate high penetration of PV generation in the grid. Implementing this control methodology does not require any extra hardware. The proposed methodology regulates the average PV power dynamically by periodically operating on and off the maximum power point (MPP) in order to inject a constant desired power into the grid. Tracking a desired power reference implies that the proposed methodology is a form of flexible power point tracking (FPPT). However, unlike a traditional FPPT, the proposed methodology also provides updated information of the available maximum PV power. Hence, the RPPT fulfills both FPPT and maximum power point tracking (MPPT) functionalities simultaneously. The proposed methodology extracts the MPP information and uses this information to calculate and regulate the amount of PV reserve power. One of the main advantages of the proposed algorithm is its applicability under partial shading conditions. Its effectiveness is demonstrated by experimental results under changing solar irradiance, grid frequency deviation, and partial shading conditions.